Low Physical Activity and Cardiorespiratory Fitness in People With Schizophrenia: A Comparison With Matched Healthy Controls and Associations With Mental and Physical Health - Scheewe, Thomas W.; Jörg, Frederike; Takken, Tim; Deenik, Jeroen; Vancampfort, Davy; Backx, Frank J. G.; Cahn, Wiepke (Frontiers in Psychiatry, 2019)
Introduction: The aim of this study was to objectively assess time spent in physical activity (PA) and sedentary behaviour (SB) in patients with schizophrenia compared to healthy controls matched for age, gender and socioeconomic status. Associations between both PA and cardiorespiratory fitness (CRF) and mental and physical health parameters in patients with schizophrenia were examined. Materials and Methods: Moderate and vigorous PA (MVPA), moderate PA, vigorous PA, total and active energy expenditure (TEE and AEE), number of steps, lying down and sleeping time was assessed with SenseWear Pro-2 body monitoring system for three 24-hour bouts in patients with schizophrenia (n=63) and matched healthy controls (n=55). Severity of symptoms (Positive and Negative Syndrome Scale and Montgomery and Åsberg Depression Rating Scale), CRF (peak oxygen uptake, VO2peak), body mass index (BMI), and metabolic syndrome were assessed. Results: Patients with schizophrenia performed less MVPA and moderate activity had lower TEE and AEE, spent more time per day lying down and sleeping, and had poorer CRF compared to healthy controls. The amount of MVPA, but especially CRF was associated with severity of negative symptoms in patients with schizophrenia. Only CRF was associated with BMI. Discussion: The current data offer further evidence for interventions aiming to increase physical activity and decrease sedentary behaviour. Given strong associations of CRF with both negative symptoms and BMI, treatment aimed at CRF-improvement may prove to be effective.